2020
DOI: 10.3897/subtbiol.33.46444
|View full text |Cite
|
Sign up to set email alerts
|

Invertebrates diversity in mountain Neotropical quartzite caves: which factors can influence the composition, richness, and distribution of the cave communities?

Abstract: Twenty caves located in a high altitudinal quartzite area in Brazil were examined for invertebrate richness and composition and in terms of environmental factors that determine community structure. We evaluate how distance, altitude, cave extension, environmental stability, number and size of cave entrances and stream presence can act on species composition and richness. The caves presented a high richness of troglophilic (463 spp.) and troglobitic species (6 spp.) in relation to other siliciclastic caves arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…(2015) and Souza‐Silva et al. (2020). Additionally, cave entrances play a key role in structuring subterranean communities as they represent the interface between epigean and hypogean ecosystems.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…(2015) and Souza‐Silva et al. (2020). Additionally, cave entrances play a key role in structuring subterranean communities as they represent the interface between epigean and hypogean ecosystems.…”
Section: Discussionmentioning
confidence: 97%
“…However, several important factors for structuring cave fauna in temperate regions, such as climatic features, ecoregions and primary productivity, and the influence of epigean ecosystems over subterranean communities, have not yet been tested in Neotropical regions (Bregović & Zagmajster, 2016;Christman et al, 2016;Culver et al, 2006;Mammola, Piano, Malard, Vernon, et al, 2019;Niemiller & Zigler, 2013). Similarly, some patterns observed for Neotropical regions have not been documented for temperate areas, such as the influence of streams and entrance features over the diversity of the terrestrial cave fauna (Prous et al, 2015;Simões et al, 2015;Souza-Silva et al, 2020a, 2020b. This is possibly due to the fact that most studies of cave fauna in temperate regions are focused on troglobitic species (Moldovan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results further demonstrate that stygofauna are reported in springs more frequently than surface fauna are reported in groundwater, in terms of both number of papers and overall numbers of species. In recent years, a growing body of literature has shown that even the occurrence of surface species in caves is often not accidental (Lunghi, Manenti & Ficetola, 2014b, a finding that has important implications for the communities of shallow subterranean habitats (Kozel et al, 2019;Lunghi, 2018;Lunghi et al, 2020;Salvidio et al, 2020;Silva, Iniesta & Ferreira, 2020). If stygofauna occur in springs and adjacent microhabitats more commonly than surface fauna occur underground, it is likely that, at least for some stygobionts, the use of the surface environment is not accidental.…”
Section: Research Disciplinementioning
confidence: 99%